EVALUATION OF SORGHUM SILAGES OF DIFFERENT GENOTYPES WITH AND WITHOUT CONDENSED TANNINS - CARNEIRO, HELOISA; SOBRINHO, FAUSTO SOUZA; RODRIGUES, JOSÉ AVELINO SANTOS; MIRANDA, JOÃO EUSTÁQUIO CABRAL; BRUM, SARAH SILVA (REVISTA BRASILEIRA DE MILHO E SORGO, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:3.0cm 3.0cm 73.7pt 3.0cm; mso-header-margin:2.0cm; mso-footer-margin:36.0pt; mso-gutter-margin:5.65pt; mso-paper-source:15 0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif]–> A total of 10 Sorghum cultivar: two lines (CMSXS114, T ) and (CMSXS165, WT ), six hybrids ( 9953101,T; 9953130,T; BR601, WT; BR701, T; BR700, T; and AG2005, WT and two varieties (BR501, WT; and BR506, WT) with 8 replications were ensiled in PVC silos of 3kg per silo for 60 days and then analyzed for condensed tannins (CT) (colorimetric analysis by the butanol-HCl method), CP, NDF, ADF, and in vitro (IVDMD-24 and 48hs) digestibilities. Condensed tannins (CT) from quebracho were purified using affinity chromatography with sephadex LH-20 and used as a standard. Low concentrations of CT have been defined as 10g/kg DM or less and medium as 10 to 40g/kg DM, and levels exceeding 40g/kg DM as high. Hybrid 9953130 had the highest concentration of CT among the sorghum silages (P< 0.05), with 10.62g/kg DM, and among the sorghum panicles, the hybrid 9953101 with 37.39g/kg DM. Differences among sorghum lines were not detected for lignin and in vitro digestibility (P> 0.09). The highest CP content was noted for line CMSXS165 (97.4g/kg; P< 0.05). Concentrations of CP in CMSXS114 (83.2g/kg), BR 700 (76.4g/kg), BR701 (80.5g/kg), and AG2005 (79.2g/kg) were above the overall mean (74.0g/kg). The in vitro digestibilities (24 and 48 hours) of the two isogenics lines CMSXS114 (T) and CMSXS165 (WT) were not different. We concluded that the CT level did not affect digestibility; however, relative CT concentrations were low. Therefore, we could not suggest significant effects of CT content on DM intake, digestibility levels or performance in cattle fed with any of these sorghum silages.